Effects of increasing L-lysine HCl on finishing pig growth performance and carcass characteristics - M De La Llata; J A Loughmiller; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
We conducted two studies to determine the effects of increasing L-lysine HCI in finishing pig diets. Experiment 1 used sorghum-soybean meal-based diets, and Exp. 2 used corn-soybean meal-based diets. Treatments included a control diet (no L-lysine HCl) or .15, .225, and .30% L-lysine HCI replacing the lysine provided by soybean meal. In Exp. 1, increasing L-lysine HCI from 0 to .150/0 had no effect on ADG, F/G, and percentage lean; however, pigs fed .225 and .30% L-Iysine HCI had poorer ADG, F/G, and percentage lean. In Exp. 2, ADG and FfG were poorer for pigs fed .225 or .30% L-lysine HCI compared with those fed the control diet or .15% L-lysine. Carcass charactistics were not affected by dietary treatnlent but tended to become poorer in pigs fed .225 or .30% L-lysine HCl. Unless diets are fortified with other amino acids, no more than .15% (3 lbfton) L-lysine HCI should be added to sorghum- and corn-soybean lneal finishing diets.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Lysine; Sorghum; Corn; Finishing pigs